Predicting Functions with Qualitative Dependent Variables Using a Logistic Regression Model: A Case Study of Emergency Surgery – Kingdom of Saudi Arabia, 1438 (The International Journal for Scientific Research, 2025)
This research aims to use the logistic regression model to predict functions with qualitative dependent variables. Data were collected and analyzed using statistical analysis software. A logistic regression model was constructed using independent variables and a qualitative dependent variable. The model's performance was evaluated using various criteria. The results showed that the logistic regression model was suitable for predicting functions with qualitative dependent variables.
Keywords: Logistic Regression; Independent Variable; Dependent Variable; Prediction; Functions